Intervensi Pekerjaan Sosial di Ruang Digital untuk Mencegah Radikalisasi Kaum Muda - Stevie Y Tarore (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2026)
Youth radicalization in the digital era reflects a significant shift in recruitment, indoctrination, and mobilization patterns that are increasingly intense through social media, online forums, and various content-sharing platforms. Digital space no longer functions solely as a means of communication but has evolved into an arena for identity formation, meaning production, and the dissemination of transnational ideologies that often exploit adolescents' psychosocial vulnerabilities. This article aims to examine a social work intervention model in the digital realm as a preventive strategy against youth radicalization, emphasizing a strengths-based approach, strengthening critical digital literacy, and building community resilience. The research uses a qualitative-descriptive approach through a systematic literature review of recent publications related to online radicalization, cyber social work practices, and community-based extremism prevention. The review indicates that social work interventions in the digital space need to be designed comprehensively and multidimensionally, encompassing early detection of extremist narratives, online psychosocial support, the development of counter-narratives based on humanitarian values, and cross-sector collaboration between social workers, educators, families, and technology platforms. Furthermore, the role of social workers as digital practitioners is crucial in creating safe, dialogical, and inclusive virtual spaces. This study emphasizes that the transformation of social work practice into the digital realm is not merely a technical adaptation, but rather a reorientation of intervention paradigms that are responsive to the dynamics of cyberculture. Therefore, preventing youth radicalization requires the integration of professional competencies, digital ethics, and participatory empowerment strategies within the online ecosystem.